ANALISIS PELAKSANAAN FULL DAY SCHOOL DI SMK NEGERI 3 PONTIANAK - Ardhani, Ryan; H. Matsum, Junaidi; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of the study is ?Analysis of the implementation of full day school at SMKN 3 Pontianak. Sub Problem is what are the school programs during the Implementation of Full Day School at SMKN 3 Pontianak. What are these programs support during the Implementation of the Full Day School at SMK N 3 Pontianak.What are the obstacles faced by the teacher during the implementation of full day school at SMKN 3 Pontianak and How the teacher handles these difficulties, What the efforts are made by the teacher making students feel comfortable during implementation of Full Day School at SMKN 3 Pontianak. What is the target of the school in the implementation of the Full Day School at SMKN 3 Pontianak. How the academic value of students during the implementation of the Full Day School at SMKN 3 Pontianak. The data collection tool used in this thesis is interview guidelines, notebook. The analysis in this thesis is presented descriptive qualitative by using informants from 1 teacher as the vice chairman curriculum and 2 teachers and 2 students SMKN 3 Pontianak. The results of the study show that during the Implementation of Full Day School at SMKN 3 Pontianak still lacking to be said as innovation in the field of education.. Suggestions to teachers are expected to be able to innovate to deliver learning with a creative learning model so students feel comfortable. Suggestions to students are expected to continue to be motivated to become superior human resources and continue to get the best education. Keywords: Implementation of Full Day School